In situ structural characterization of electrochemical systems using synchrotron-radiation techniques - De Marco, Roland; Veder, Jean-Pierre (Elsevier Science B.V., 2010)
In recent times, in situ synchrotron-radiation techniques have been used extensively in studies of scientifically and technologically important electrochemical systems. In this review, we showcase the power of electrochemical measurement, either active or passive, in combination with in situ synchrotron-radiation techniques, using research reported on battery systems, corroding metals, ion-selective electrodes and fuel cells. Moreover, we review the specialized electrochemical cells and general design principles utilized by electrochemical synchrotron researchers.